Transient sleep apnea results in long-lasting increase in β-amyloid generation and tau hyperphosphorylation - Takeru Nagayama; Sosuke Yagishita; Megumi Shibata; Akiko Furuno; Takashi Saito; Takaomi C. Saido; Shuji Wakatsuki; Toshiyuki Araki (Neuroscience Research)
Sleep apnea is regarded as an important risk factor in the pathogenesis of Alzheimer disease (AD). Chronic intermittent hypoxia treatment (IHT) given during the sleep period of the circadian cycle in experimental animals is a well-established sleep apnea model. Here we report that transient IHT for 4 days on AD model mice causes Aβ overproduction 2 months after IHT presumably via upregulation of synaptic BACE1, side-by-side with tau hyperphosphorylation. These results suggest that even transient IHT may be sufficient to cause long-lasting changes in the molecules measured as AD biomarkers in the brain.